Repurposing the Antidiabetic Drugs Glyburide, Gliquidone, and Glipizide in Combination with Benznidazole for Trypanosoma cruzi Infection - Citlali Vázquez; Rusely Encalada; Isabel Jiménez-Galicia; Rogelio Gómez-Escobedo; Gildardo Rivera; Benjamín Nogueda-Torres; Emma Saavedra (Pharmaceuticals)
Infection with the protozoan parasite Trypanosoma cruzi causes human Chagas disease. Benznidazole (BNZ) and nifurtimox are the current drugs for the treatment; however, they induce severe adverse side effects in patients; therefore, there is a need to improve the treatment effectiveness and efficiency of these drugs for its safer use. Background/Objective: Glyburide, glipizide, and gliquidone, hypoglycemic drugs for diabetes treatment, were previously predicted to bind to dihydrofolate reductase-thymidylate synthase from T. cruzi by in silico docking analysis; they also showed antiproliferative effects against T. cruzi epimastigotes, the stage of the insect vector. In the present study, the potential parasiticidal effect of these antidiabetic drugs was tested in monotherapy and bi-therapy with BNZ in human cells in vitro and in animals. Methods: Evaluation was performed in (a) a model of in vitro infection of T. cruzi trypomastigotes using human fibroblasts as host cells and (b) in mice infected with T. cruzi. Results: The antidiabetic drugs in monotherapy showed antiparasitic effects in preventing infection progression (trypomastigotes release), with an IC50 of 8.4–14.3 µM in comparison to that of BNZ (0.26 µM) in vitro. However, in bi-therapy, the presence of just 0.5 or 1 µM of the antidiabetics decreased the BNZ IC50 by 5–10 times to 0.03–0.05 µM. Remarkably, the antidiabetic drugs in monotherapy decreased the infection in mice by 40–60% in a similar extent to BNZ (80%). In addition, the combination of BNZ plus antidiabetics perturbed the antioxidant metabolites in epimastigotes. Conclusions: These results identified antidiabetics as potential drugs in combination therapy with BNZ to treat T. cruzi infection.